2019
DOI: 10.1038/s41598-019-38841-y
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Stimulation by Pyridostigmine Bromide Before Myocardial Infarction Prevent Cardiac and Autonomic Dysfunction

Abstract: Inflammatory processes and cardiovascular autonomic imbalance are very relevant characteristic of the enormous dynamic process that is a myocardial infarction (MI). In this sense, some studies are investigating pharmacological therapies using acetylcholinesterase inhibitors, such as pyridostigmine bromide (PYR), aiming to increase parasympathetic tone after MI. Here we hypothesized that the use of PYR before the MI might bring an additional positive effect to the autonomic function, and consequently, in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The reduction of the LF/HF ratio indicated increased parasympathetic activity and led to improved heart rate variability in MI rats. 28,30,31,36,38,56 Similarly, pyridostigmine increased baroreflex sensitivity in MI rats. 31,35,37,38,56 All these reported benefits could contribute to attenuating the severity of MI.…”
Section: Of 24mentioning
confidence: 91%
See 4 more Smart Citations
“…The reduction of the LF/HF ratio indicated increased parasympathetic activity and led to improved heart rate variability in MI rats. 28,30,31,36,38,56 Similarly, pyridostigmine increased baroreflex sensitivity in MI rats. 31,35,37,38,56 All these reported benefits could contribute to attenuating the severity of MI.…”
Section: Of 24mentioning
confidence: 91%
“…14 Use of an AChE inhibitor has been shown to improve cardiac autonomic balance by increasing parasympathetic tone and suppressing sympathetic tone in rats with MI. 13,36,[54][55][56] Heart rate variability is an indirect method that is used to determine cardiac autonomic function. 53 Several studies reported that AChE inhibitors suppress neurohumoral activation and sympathetic tone, thus improving cardiac autonomic function and cardiac remodelling in MI rats.…”
Section: Of 24mentioning
confidence: 99%
See 3 more Smart Citations